Human Immunodeficiency Virus transmission by HIV Risk Group and Along the HIV Care Continuum: A Contrast of 6 US Cities. (1st February 2022) - Zang, Xiao; Mah, Cassandra; Quan, Amanda My Linh; Min, Jeong Eun; Armstrong, Wendy S.; Behrends, Czarina N.; Del Rio, Carlos; Dombrowski, Julia C.; Feaster, Daniel J.; Kirk, Gregory D.; Marshall, Brandon D.L.; Mehta, Shruti H.; et al.
Abstract : Background: Understanding the sources of HIV transmission provides a basis for prioritizing HIV prevention resources in specific geographic regions and populations. This study estimated the number, proportion, and rate of HIV transmissions attributable to individuals along the HIV care continuum within different HIV transmission risk groups in 6 US cities. Methods: We used a dynamic, compartmental HIV transmission model that draws on racial behavior–specific or ethnic behavior–specific and risk behavior–specific linkage to HIV care and use of HIV prevention services from local, state, and national surveillance sources. We estimated the rate and number of HIV transmissions attributable to individuals in the stage of acute undiagnosed HIV, nonacute undiagnosed HIV, HIV diagnosed but antiretroviral therapy (ART) naïve, off ART, and on ART, stratified by HIV transmission group for the 2019 calendar year. Results: Individuals with undiagnosed nonacute HIV infection accounted for the highest proportion of total transmissions in every city, ranging from 36.8% (26.7%–44.9%) in New York City to 64.9% (47.0%–71.6%) in Baltimore. Individuals who had discontinued ART contributed to the second highest percentage of total infections in 4 of 6 cities. Individuals with acute HIV had the highest transmission rate per 100 person-years, ranging from 76.4 (58.9–135.9) in Miami to 160.2 (85.7–302.8) in Baltimore. Conclusion: These findings underline the importance of both early diagnosis and improved ART retention for ending the HIV epidemic in the United States. Differences in the sources of transmission across cities indicate that localized priority setting to effectively address diverse microepidemics at different stages of epidemic control is necessary. Abstract : Supplemental Digital Content is Available in the Text.